2015
DOI: 10.1177/1474515114566737
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depression among amyloid light-chain cardiac amyloidosis patients: The role of life satisfaction

Abstract: Overall, findings highlight the importance of subjective well-being (e.g. life satisfaction) to reduce anxious and depressive symptoms and to improve general health in AL patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 21 publications
0
9
0
1
Order By: Relevance
“…Among patients with cardiovascular disease, a significant correlation between life satisfaction and depression has been established (Steca et al, 2013). A study of amyloid light-chain cardiac amyloidosis has shown the association between depression and anxiety and life satisfaction (Smorti et al, 2016). Life satisfaction, the general affective evaluation of a person’s life (Pavot et al, 1991), is an important component of subjective well-being (Yang & Srinivasan, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Among patients with cardiovascular disease, a significant correlation between life satisfaction and depression has been established (Steca et al, 2013). A study of amyloid light-chain cardiac amyloidosis has shown the association between depression and anxiety and life satisfaction (Smorti et al, 2016). Life satisfaction, the general affective evaluation of a person’s life (Pavot et al, 1991), is an important component of subjective well-being (Yang & Srinivasan, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative research indicates that patients with AL amyloidosis experience substantial burden that can lead to impairment in daily functioning [10, 11]. Furthermore, AL amyloidosis can lead to anxiety, frustration, and depression as patients grapple with the gravity and rarity of their condition [10, 12]. Although limited, quantitative studies provide evidence of deficits in both physical and mental aspects of HRQoL [13, 14].…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, the results of the current study provided evidence of the content validity of the SF-36v2 as an appropriate measure for assessing the impact of HRQoL in patients with AL amyloidosis. The range and severity of symptoms of this disease, as well as the side effects of treatment, have been shown to greatly impact HRQoL [ 8 , 10 , 11 , 14 ], clearly warranting more standardized use of HRQoL measures that are capable of capturing the impacts of such diverse experiences.…”
Section: Discussionmentioning
confidence: 99%
“…The semi-structured interview guides that were used for each part of the study were informed by a thorough literature review of published reports of HRQoL in patients with AL amyloidosis [ 8 11 , 13 , 14 ]. Inclusion criteria were set so that all patients were at least 18 years of age, self-reported having been diagnosed with AL amyloidosis by a physician, and were able to complete the interview in English.…”
Section: Methodsmentioning
confidence: 99%